Gastroesophageal reflux in children with functional constipation - Maşallah Baran; Funda ÖZGENÇ; Çiğdem ARIKAN; Murat Çakır; Çiğdem ÖMÜR ECEVİT; Sema Aydoğdu; Raşit Vural YAĞCI (Turkish Journal of Gastroenterology, 2019)
-